2015
DOI: 10.3171/2014.10.peds14117
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of children with severe traumatic brain injury who are treated with decompressive craniectomy

Abstract: OBJECT Decompressive craniectomy (DC) for the management of severe traumatic brain injury (TBI) is controversial. The authors sought to determine if DC improves the outcome of children with severe TBI. METHODS In a retrospective, case-control study, medical records of all patients admitted to the pediatric ICU between May 1998 and May 2008 with severe TBI and treated with DC were identified and matched t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 29 publications
3
16
0
3
Order By: Relevance
“…Of note, as it has been recently clarified, the optimal control of ICP cannot exclude the presence of undergoing cerebral injuries and cannot guarantee a good neurological outcome. 24,25 Some pediatric and adult studies have demonstrated that craniectomy was associated with optimal neurological outcome, 3,4,[26][27][28][29][30] while, on the contrary, there are studies that have shown that patients underwent DC had poor outcome compared with medical treatment. 31,32 In both recent RCTs, craniectomy patients presented significantly less favorable outcome at six months postinjury.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, as it has been recently clarified, the optimal control of ICP cannot exclude the presence of undergoing cerebral injuries and cannot guarantee a good neurological outcome. 24,25 Some pediatric and adult studies have demonstrated that craniectomy was associated with optimal neurological outcome, 3,4,[26][27][28][29][30] while, on the contrary, there are studies that have shown that patients underwent DC had poor outcome compared with medical treatment. 31,32 In both recent RCTs, craniectomy patients presented significantly less favorable outcome at six months postinjury.…”
Section: Discussionmentioning
confidence: 99%
“…Az sayıda çalışma bu tedavinin ağır travmatik beyin hasarı sonrası çocuklarda uzun dönemde pozitif etkisini göstermiştir. 7,9 Taylor ve ark. 'nın 7 ağır kafa travmalı bir yaşın üzerinde 27 çocuk hastayla yaptıkları çalışmada bitemporal kraniektomi ile tıbbi tedavi karşılaştırılmıştır.…”
Section: Discussionunclassified
“…Bazı çalışmalar da erken cerrahinin daha iyi sonuçlar verdiğini göstermiştir. 7,9,11,12 Mhanna ve ark. 'nın 9 çocuk hastalarda yaptıkları çalışmada dekompresif kraniektomi yapılan 17 hasta ile işlemin uygulanmadığı 17 hasta kontrol grubu olarak değerlendirilmiştir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Similarly, TBI represents a significant cause of morbidity and mortality in children admitted to the PICU (31,36,42,100). As shown in other fields, protocolized care and adherence to guidelines, even if of low evidence level, can be associated with improved outcomes.…”
Section: Neurologic Outcomes Following Picu Carementioning
confidence: 99%